2018
DOI: 10.1002/eji.201747195
|View full text |Cite
|
Sign up to set email alerts
|

CXCL4 is a novel inducer of human Th17 cells and correlates with IL‐17 and IL‐22 in psoriatic arthritis

Abstract: CXCL4 regulates multiple facets of the immune response and is highly upregulated in various Th17‐associated rheumatic diseases. However, whether CXCL4 plays a direct role in the induction of IL‐17 production by human CD4+ T cells is currently unclear. Here, we demonstrated that CXCL4 induced human CD4+ T cells to secrete IL‐17 that co‐expressed IFN‐γ and IL‐22, and differentiated naïve CD4+ T cells to become Th17‐cytokine producing cells. In a co‐culture system of human CD4+ T cells with monocytes or myeloid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…Moreover, studies on T-cells indicated that CXCL4 inhibits proliferation and IL-2 production on activated T-cells, induces regulatory (CD4 + CD25 + ) T-cell proliferation while inhibiting non-regulatory (CD4 + CD25 − ) T-cell proliferation and drives T-cell polarization (13). CXCL4 has also been implicated in the pathology of a variety of inflammatory diseases including myelodysplastic syndromes, malaria, HIV-1, atherosclerosis, inflammatory bowel disease, and rheumatoid arthritis (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). For example, levels of CXCL4 were significantly higher in inflammatory bowel disease and giant cell arteritis than in the non-inflammatory controls (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies on T-cells indicated that CXCL4 inhibits proliferation and IL-2 production on activated T-cells, induces regulatory (CD4 + CD25 + ) T-cell proliferation while inhibiting non-regulatory (CD4 + CD25 − ) T-cell proliferation and drives T-cell polarization (13). CXCL4 has also been implicated in the pathology of a variety of inflammatory diseases including myelodysplastic syndromes, malaria, HIV-1, atherosclerosis, inflammatory bowel disease, and rheumatoid arthritis (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). For example, levels of CXCL4 were significantly higher in inflammatory bowel disease and giant cell arteritis than in the non-inflammatory controls (24).…”
Section: Introductionmentioning
confidence: 99%
“…Monocyte-derived dendritic cells (moDCs) can be differentiated in vitro by culturing monocytes isolated from human donors and are considered as DC model that mimics in vivo DC biology. Previously, we investigated whether circulating CXCL4 potentiates aberrant TLR-mediated responses and T-cell dysregulated responses observed in autoimmune diseases ( 14 , 20 ). Considering the presence of CXCL4 during early inflammation and its role in modulating key immune functions, we postulated that CXCL4 might constitute the link between inflammation and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The results of KEGG pathway enrichment analysis demonstrate that Th17 differentiation is related to the protective effect of hydrogen-rich water. Th17 cells are a subset of T cells associated with many inflammatory and autoimmune diseases that secrete inflammatory factors such as IL-17 and IL-22 21-22.There is data showing that Th17 cells are closely related to the occurrence of renal ischemia-reperfusion injury, and its expression is significantly increased in ischemia-reperfusion tissues 23. Table 1 and 3 show that the proteins involved in the differentiation of Th17 cells include IL-2Ra, IL-17F and IL-22, and the expression levels of these three proteins are decreased compared with those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Whether SpA-associated joint-infiltrating lymphocytes enter tissues as already activated and functionally mature cells also remains an open question. Relatedly, CXCL4 was recently identified as a novel potent inducer of human T H 17 cells enriched in PsA joints, and CXCL4 levels also positively correlated with disease severity, thus suggesting a CXCL4-driven local boost of T H 17 cells ( 143 ).…”
Section: Concluding Remarks: Whodunit?mentioning
confidence: 98%